Influência de diferentes períodos de chuva após a aplicação de Clethodim, Quizalofope - P- Metilico e Haloxifope em pós emergência no controle de plantas daninhas - Silva, Breno Araguaia Souza [UNESP] (2014)
The study aimed to evaluate the influence of different time intervals of rainfall after the application of herbicide clethodim, haloxyfope and quizalofope-p-methyl, in post-emergence control of four weed species: B. decumbens, B. plantaginea, Cenchrus echinatus and Zea mays on soybeans. The experimental design was completely randomized and treatments arranged in a factorial scheme 3 x 6 (three herbicides and six time intervals of rain), totaling eighteen treatments and four replications for each weed species. Four experiments were conducted at a greenhouse with two plants per pot in the municipality of Pereiras, SP. Herbicide applications were made at different times during the day, in order to obtain different time intervals to simulate rain on the plants. Control evaluations at days 3, 7, 14, 21 and 28, were performed after application (DAA) of herbicides. After herbicide application the weeds were submitted to a slide of rain of 20 mm in five time intervals (15, 30, 60, 120 and 240 min) and no rain (herbicide treatment control), plus an additional treatment with no rain and without herbicide (control). At the end of each assessment for each species was determined the accumulation of plant biomass. With the results above it was found that the ranges of rain negatively interferes with the action of herbicides to control plants and herbicide quizalofope-p-methyl and haloxyfope were the most outstanding in plants control.